Modelling and Control of Automatic Generation Control of Upper Trishuli 3A Hydropower Plant - Yadav, Narendra; Adhikari, Sujan; Mishra, Akhileshwor (Journal of Advanced College of Engineering and Management, 2025)
Only producing electricity is insufficient due to rising load demands and mismatches between generation and load, particularly in the contemporary power system of today. The power system’s frequency becomes unstable due to a mismatch between the load and generation (active power). Automatic Generation Control (AGC) handles this crucial and difficult task, which involves quickly returning the power system’s frequency to its normal value. In order to minimize the settling time of the frequency response of the UT3A hydropower plant connected to Integrated Nepal Power System(INPS) in a two area power system, this effort entails modeling and managing the AGC. In order to minimize ACE and stabilize the frequency response of the UT3A hydropower plant in the AGC model, three scenarios are taken into consideration based on the step load input to the system with PID, PSO tuned SSSC, FLC, and ANFIS controller. In the UT3A hydropower facility, ANFIS is proven to be the best controller for minimizing frequency response settling time. The issue of frequency instability, which results in system outages because synchronization breaks in an interconnected system, is also better addressed in this work.